Vegetables containing phytochemicals with potential anti-obesity properties: A review - Williams, D.; Edwards, D.; Hamernig, I.; Jian, Le; James, Tony; Johnson, Stuart; Tapsell, L. (Elsevier, 2013)
The incidence of obesity is rising worldwide at an alarming rate and is becoming a major public health concern with incalculable social and economic costs. Studies have exposed the relationship between the adiposity, inflammation and the development of other metabolic disorders, so dietary factors that influence some or all of these are of interest. Dietary phytochemicals appear to be able to target different stages of the adipocyte (fat cell) lifecycle. For example, several classes of polyphenols have been implicated in suppressing the growth of adipose tissue through modifying the adipocyte lifecycle. Many dietary phytochemicals also have strong anti-inflammatory activity, but the amount present in plants varies and may be affected by processing. In this review we summarise the likely mechanisms of action of plant phytochemicals. We highlight the major vegetable sources of polyphenols, including those with possible synergistic attributes, discuss the variation in polyphenol levels and their distribution in cultivars and outline the effects of food processing. The identification and characterisation of the anti-obesogenic properties of phytochemicals in vegetables, as well as an appreciation of the effect of cooking on phytochemical content provide significant new information supporting dietary guidelines that encourage vegetable consumption for the prevention and management of lifestyle related disease.